Oral fexinidazole for late-stage African Trypanosoma brucei gambiense trypanosomiasis: a pivotal multicentre, randomised, non-inferiority trial. Issue 10116 (13th January 2018) - Mesu, Victor Kande Betu Ku; Kalonji, Wilfried Mutombo; Bardonneau, Clélia; Mordt, Olaf Valverde; Blesson, Séverine; Simon, François; Delhomme, Sophie; Bernhard, Sonja; Kuziena, Willy; Lubaki, Jean-Pierre Fina; Vuvu, Steven Lumeya; Ngima, Pathou Nganzobo; et al.
Summary: Background: Few therapeutic options are available to treat the late-stage of human African trypanosomiasis, a neglected tropical disease, caused by Trypanosoma brucei gambiense (g-HAT). The firstline treatment is a combination therapy of oral nifurtimox and intravenous eflornithine that needs to be administered in a hospital setting by trained personnel, which is not optimal given that patients often live in remote areas with few health resources. Therefore, we aimed to assess the safety and efficacy of an oral regimen of fexinidazole (a 2-substituted 5-nitroimidazole with proven trypanocidal activity) versus nifurtimox eflornithine combination therapy in patients with late-stage g-HAT. Methods: In this randomised, phase 2/3, open-label, non-inferiority trial, we recruited patients aged 15 years and older with late-stage g-HAT from g-HAT treatment centres in the Democratic Republic of the Congo (n=9) and the Central African Republic (n=1). Patients were randomly assigned (2:1) to receive either fexinidazole or nifurtimox eflornithine combination therapy according to a predefined randomisation list (block size six). The funder, data management personnel, and study statisticians were masked to treatment. Oral fexinidazole was given once a day (days 1–4: 1800 mg, days 5–10: 1200 mg). Oral nifurtimox was given three times a day (days 1–10: 15 mg/kg per day) with eflornithine twice a day as 2 h infusions (days 1–7: 400 mg/kg per day). The primary endpoint was success at 18 months (ie, deemed as patients being alive, having no evidence of trypanosomes in any body fluid, not requiring rescue medication, and having a cerebrospinal fluid white blood cell count ≤20 cells per μL). Safety was assessed through routine monitoring. Primary efficacy analysis was done in the modified intention-to-treat population and safety analyses in the intention-to-treat population. The acceptable margin for the difference in success rates was defined as 13%. This study has been completed and is registered withClinicalTrials.gov, numberNCT01685827 . Findings: Between October, 2012, and November, 2016, 419 patients were pre-screened. Of the 409 eligible patients, 14 were not included because they did not meet all inclusion criteria (n=12) or for another reason (n=2). Therefore, 394 patients were randomly assigned, 264 to receive fexinidazole and 130 to receive nifurtimox eflornithine combination therapy. Success at 18 months was recorded in 239 (91%) patients given fexinidazole and 124 (98%) patients given nifurtimox eflornithine combination therapy, within the margin of acceptable difference of −6·4% (97·06% CI −11·2 to −1·6; p=0·0029). We noted no difference in the proportion of patients who experienced treatment-related adverse events (215 [81%] in the fexinidazole group vs 102 [79%] in the nifurtimox eflornithine combination therapy group). Treatment discontinuations were unrelated to treatment (n=2 [1%] in the fexinidazole group). Temporary nifurtimox eflornithine combination therapy interruption occurred in three (2%) patients. 11 patients died during the study (nine [3%] in the fexinidazole group vs two [2%] in the nifurtimox eflornithine combination therapy group). Interpretation: Our findings show that oral fexinidazole is effective and safe for the treatment of T b gambiense infection compared with nifurtimox eflornithine combination therapy in late-stage HAT patients. Fexinidazole could be a key asset in the elimination of this fatal neglected disease. Funding: Drugs for Neglected Diseases initiative .